Implementation of a Process Orchestration Model in a Service Oriented Holonic Manufacturing System. Issue 3 (2015) - Francisco Gamboa, Q.; Cardin, Olivier; L'Anton, Anne; Castagna, Pierre
Abstract: Process models are usually represented by linear sequences, where the order of the conforming operations is fixed a priori. In a FMS, flexibility can be considered as proportional to the number of alternatives the system has when a decision needs to be made. Considering only flexibility related to the choice and the order in which the products are treated on machines is therefore limitative when the design of the products could enable flexible recipes, where groups of operations could be permuted according to the state of the system. The objective of this paper is to describe the implementation of service and process models as well as the orchestration of such processes at a product level.